Use of glycated hemoglobin (HbA1c) and impaired glucose tolerance in the screening of undiagnosed diabetes in the Malaysian population - Qvist, R.; Ismail, I.S.; Chinna, K.; Muniandy, S. (2008)
Although HbA1c is widely accepted as a useful index of mean blood glucose in type 2 diabetic patients its usefulness as screening test for diabetes has been controversial. The present study was undertaken to determine whether the level of HbA1c predicted diabetes in a prediabetic group of subjects. Plasma lipids, oral glucose tolerance, HbA1c was determined in 90 normal control subjects, 57 offspring of one type 2 diabetes mellitus parent and 11 diagnosed type 2 diabetes mellitus individuals. The mean age of participants was 44.5 yrs (not significantly different amongst the three groups) and the mean body mass index was 26.8 (not significantly different amongst the three groups). Two hours after a 75 g glucose challenge, the offspring had a significantly higher plasma glucose level (mean = 7.1 mmol/L, p value = 0.002) than the normals. Similarly the HbA1c values were higher in the offspring than in the normals (mean = 5.78, p value =0.016). Besides the significantly higher values for oral glucose tolerance test and HbA1c , the diabetics also were significantly higher for triglycerides (mean = 2.25mmol/L), total cholesterol (mean = 6.24mmol/L) and systolic blood pressure (mean = 138.45mm Hg) than the offspring (P value = 0.031, 0.006, 0.010) and the normals (P value = 0.026, 0.018, 0.002) respectively. The mean values of diastolic blood pressure, LDL cholesterol and HDL cholesterol were not significantly different amongst the three groups.